Model Optimasi Biaya Produksi Pada Jaringan Rantai Pasok Karet Rakyat Menggunakan Pemrograman Linier - Fido Rizki; M Izman Herdiansyah; Darius Antoni (STMIK Budi Darma, 2021)
The purpose of this research is to optimize the smallholder rubber supply chain with the sample data in Kabupaten Musirawas, The main problem in the people's rubber plantation in Musirawas Regency that has not been able to be resolved include the supply chain system that is not optimal and efficient. Based on the results of the author's observations and interviews at the Plantation Office of Kabupaten Musirawas, there are three supply chain channels in Kabupaten Musirawas, the first is through the channel of Planters - Village Collectors - Subdistrict Collectors - Bokar Processing Factories, the second is Planters - Subdistrict Collectors - Bokar Processing Plants and the third is Planters - UPPB - Bokar Processing Factory, this study uses a linear programming method in determining the most efficient and profitable supply chain in Kabupaten Musirawas, For optimization testing the author uses the LINGO 13.0 software, The results of tests that have been carried out using LINGO software show that the optimal and efficient supply chain is channel 3